Human Antibody Response to Aedes albopictus Salivary Proteins: A Potential Biomarker to Evaluate the Efficacy of Vector Control in an Area of Chikungunya and Dengue Virus Transmission. (13th April 2014) - Doucoure, Souleymane; Mouchet, François; Cornelie, Sylvie; Drame, Papa Makhtar; D'Ortenzio, Eric; DeHecq, Jean Sébastien; Remoue, Franck
Abstract : Aedes borne viruses represent public health problems in southern countries and threat to emerge in the developed world. Their control is currently based on vector population control. Much effort is being devoted to develop new tools to control such arbovirus. Recent findings suggest that the evaluation of human antibody (Ab) response to arthropod salivary proteins is relevant to measuring the level of human exposure to mosquito bites. Using an immunoepidemiological approach, the present study aimed to assess the usefulness of the salivary biomarker for measuring the efficacy of Ae. albopictus control strategies in La Reunion urban area. The antisaliva Ab response of adult humans exposed to Ae. albopictus was evaluatedbefore and after vector control measures. Our results showed a significant correlation between antisaliva Ab response and the level of exposure to vectors bites. The decrease of Ae . albopictus density has been detected by this biomarker two weeks after the implementation of control measures, suggesting its potential usefulness for evaluating control strategies in a short time period. The identification of species specific salivary proteins/peptides should improve the use of this biomarker.